Relationship of Physical Properties and Wettability of Jabon Wood (Anthocephalus chinensis (Lamk.) A. Rich. Ex. Walp. Syn.) Towards Resistance of Adhesive (Journal of Wetlands Environmental Management, 2023)
The objective of the study was to determine the relationship between physical properties (specific gravity, moisture content, and shrinkage) and bonding strength of Jabon wood; and between wettability and bonding strength.  The results showed that the variable of bonding strength and physical properties had a close relationship, it was shown by R2 = 87.5% and r = 0.93, especially on tangential shrinkage.  In addition to physical properties, the wetting property of Jabon sawdust can be used to estimate bonding strength.